Technological prospecting of music therapy in Alzheimer's disease (Research, Society and Development, 2021)
Alzheimer's disease (AD) is characterized by cognitive impairment and progressive memory loss and drug treatments have limited efficacy. Thus, non-pharmacological interventions, such as music therapy, have shown to be promising as supporting pharmacological treatment and, therefore, may arouse commercial interest regarding the development of this type of product. Thus, this study aims to carry out a patentometric survey on patent registrations with music therapy in the treatment of AD. A systematic search was carried out from 2000 to 2020 on the Orbti-Questel website, searching for documents referring to music therapies in AD. The terms “Alzheimer music methodology active therapy” and “Alzheimer music methodology passive therapy” were used. After searching, reading, and excluding duplicate results, we found four patent families referring to music therapy in AD and all were selected as a result, which was considered little compared to the number of studies published on the subject.